Price Rigidity and Monetary Non-Neutrality in Developing Countries: Evidence from Nigeria - Urama, Nathaniel E.; Oduh, Moses O.; Nwosu, Emmanuel O.; Odo, Augustine C. (International Journal of Economics and Financial Issues, 2013)
In an attempt to find out the degree of monetary non-neutrality in Nigeria we started from finding out the size of price rigidity in the country. Computation with Ball and Romer method showed that price rigidity is optimal decision for firms in Nigeria only when the menu cost is well above 2.28% of the firm’s revenue which is on the high side, showing the likelihood of weak price rigidity in the country. Confirming this, the IRFs of the SVAR shows that the response of inflation to nominal shock has only one period lag. These combined results led to a small though persistent response of output to the nominal shock. The result of the study therefore points towards large nominal and small real effect of monetary policy in Nigeria and conclude that monetary policy will be a better option for contractionary plan but not for an expansionary plan. Keywords: Price rigidity; menu cost; monetary non-neutrality; monetary policy JEL Classifications: D40; E52; E63